EDUKASI PENINGKATAN NILAI PRODUK DI DESA KUNCEN KECAMATAN PADANGAN - Oktavianus Cahya Anggara; Bagus Dwi Septian; Sriyatun; Rizal Friski; Yudha Pratama; Liana Anggraini; Endah Arum Sari (Politeknik Negeri Sriwijaya, 2023)
The socialization program for making soy milk and preserving tofu using lime and salt carried out by the 13th KKN-TK Group of Bojonegoro University aims to provide economic innovation to the people of Kuncen Village. This activity explained the steps of the program, starting from making soy milk into a fast food drink to the procedure for preserving tofu with lime. Educational presentations about the benefits of soy milk and procedures for preserving tofu were also delivered to PKK mothers. Packaging samples and logo designs for soy milk and tofu are also provided. This program is expected to improve the economy and provide product characteristics to Kuncen Village. In conclusion, this program has the potential to provide economic benefits and provide solutions to the problem of perishable tofu